Fabrication of Porous N-rich Carbon Electrocatalysts from Pyrolysis of PANI-Encapsulated CeO2 for Enhanced Oxygen Reduction Reaction. Issue 4 (14th April 2021) - Yanhua, Lei; Tan, Ning; Huo, Da; Ding, Mengchao; Zhang, Yuliang; Liu, Tong; Yu, Ruixuan; Cheng, Sha; Fan, Runhua
Abstract : The oxygen reduction reaction (ORR) is a crucial cathodic process and a technology providing renewable energy. It is essential to create ORR catalysts not containing noble metals yet still affordable and possessing high-efficiency and long-term durability. Therefore, this work developed a highly porous N-doped carbon catalyst embedded with CeO2 nanoparticles (NPs). This composite catalyst was synthesized by pyrolysis of PANI-encapsulated CeO2 NPs (CeO2 /PANI) combined with in situ polymerization. The resulting catalyst exhibited an outstanding ORR performance with 0.94 and 0.81 mV onset and positive half-wave potentials, respectively, and 5.52 mA cm −2 diffusion-limited current density. The catalyst also demonstrated excellent stability. These exceptional characteristics indicate that a synergy of the N-doped carbon and CeO2 NPs provide a novel strategy of fabrication of novel ORR catalysts without using noble-metals for applications related to fuel cells and metal-air batteries.